Ceramic sealed vacuum electrode and brazing method
By using mechanical ball milling mixing of rare earth element La powder and AgCuTi active brazing and Ti metal film wetting technology in the brazing process of ceramic sealed vacuum electrodes, the cracks and sealing deterioration caused by excessive thermal stress of ceramic sealed vacuum electrodes are solved, and the mechanical properties of the welds are improved and the reliability and stability of the equipment are guaranteed.
Patent Information
- Application Number
- CN202510083787.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-20
AI Technical Summary
During the brazing process, the thermal stress caused by the difference in the thermal expansion coefficient of the material during the ceramic sealed vacuum electrode is too large, resulting in cracks and poor sealing properties, affecting the reliability and service life of the equipment.
The rare earth element La powder is used to mechanically mix with AgCuTi active brazing to form Ag-based composite brazing material, and brazed through a vacuum brazing furnace, and wetted on the ceramic block with Ti metal film to enhance binding force.
It effectively avoids the composition segregation during La element smelting, refines the hard and brittle phase in the weld, reduces the residual thermal stress of the weld, improves the shear strength of the weld, and ensures the reliability and stability of the ceramic sealed vacuum electrode.
Smart Images

Figure CN119905844A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vacuum brazing, in particular to a ceramic sealed vacuum electrode and a brazing method. Background Art
[0002] Ceramic sealed vacuum electrodes are widely used in vacuum equipment, electron tubes, vacuum circuit breakers, and the nuclear industry. They are used to transmit electrical signals in a vacuum environment while providing highly reliable sealing.
[0003] Ceramic sealed vacuum electrodes are usually connected by brazing, but due to the large difference in thermal expansion coefficients between the insulating ceramic and the conductive core column, a large thermal stress will be generated during the brazing process. Excessive thermal stress will cause cracks in the ceramic sealed vacuum electrode during service, resulting in poor sealing, which in turn affects the reliability and service life of the equipment.
[0004] At present, in order to reduce the residual thermal stress and ensure the sealing of the ceramic sealed vacuum electrode under high temperature and high pressure environment, a particle phase with a thermal expansion coefficient between the solder and the ceramic base material can be added to the solder to form a composite solder, thereby reducing the difference in thermal expansion coefficient between the solder as a whole and the ceramic base material and reducing the residual thermal stress. However, excessive content of the particle phase will cause the wettability of the composite solder to deteriorate, resulting in a decrease in the bonding strength of the brazing part of the ceramic sealed vacuum electrode.
[0005] The brazing alloy structure can be regulated by melting and modifying AgCuTi solder with the rare earth element La. However, the diffusion rate of La in the solder is slow, and there may be a phenomenon of excessive or insufficient La in some parts, which affects the brazing performance of the solder. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a ceramic sealed vacuum electrode and a brazing method.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A ceramic sealed vacuum electrode, the ceramic sealed vacuum electrode passes through a flange; the ceramic sealed vacuum electrode comprises a conductive core column, a ceramic block sleeved on the conductive core column, a first sleeve and a second sleeve; the first sleeve and the second sleeve are both made of Kovar alloy; the ceramic block comprises a cylinder, a circular plate arranged at the upper end of the cylinder and an annular plate arranged in the middle of the cylinder, the inner side surface of the first sleeve is respectively brazed to the lower surface and the outer side surface of the circular plate, and the inner side surface of the second sleeve is respectively brazed to the lower surface and the outer side surface of the annular plate; a stepped hole is provided on the flange, the outer side surface of the first sleeve is brazed to the upper part of the inner side surface of the stepped hole, and the outer side surface of the second sleeve is brazed to the lower part of the inner side surface of the stepped hole.
[0009] The first and second sleeves are made of Kovar alloy, which has good thermal expansion matching performance and can effectively relieve the residual stress between the flange and the ceramic block. The stepped hole supports the ceramic block through its unique internal stepped structure.
[0010] Preferably, the conductive core column is made of molybdenum, stainless steel or oxygen-free copper.
[0011] Preferably, the ceramic block is made of Al2O3 or zirconium oxide material.
[0012] Preferably, the brazing adopts Ag-based composite brazing material, which is composed of mixed brazing material and organic binder, the mass percentage of the mixed brazing material is 85%-90%, and the balance is organic binder;
[0013] The mixed solder consists of rare earth element La powder and AgCuTi active solder, wherein the mass percentage of the rare earth element La powder in the mixed solder is 0.5%-2.5%, and the balance is AgCuTi active solder; the rare earth element La powder and the AgCuTi active solder are mechanically ball-milled to obtain the mixed solder, and the mixed solder is mixed with an organic binder to obtain the prepared Ag-based composite solder.
[0014] After adding rare earth element La powder to AgCuTi active solder, La element will form tiny nucleation points in the molten AgCuTi solder, increase the nucleation rate of intermetallic compounds, and inhibit their growth and coarsening; the addition of La element reduces the energy of interfacial reaction, and its strong reducing property helps to control the reaction rate of Cu element and Ti element; La element can change the formation temperature and morphology of intermetallic compounds in the solder, making them nucleate at a lower temperature and form a finer particle structure.
[0015] The La element reacts with O2 in the AgCuTi active solder to reduce the oxidation of the active element Ti; La reacts with O to form rare earth oxides, which serve as nucleation points for the growth of the Cu-Ti phase and promote the heterogeneous nucleation of the Cu-Ti phase; the atomic radius of the La element is larger than that of the Cu element, and the solid solubility of the La element in the AgCuTi active solder is relatively low. The La element and its compounds are distributed at the interface, which reduces the grain boundary energy and the driving force for grain growth, effectively preventing the growth of grains and maintaining the fine morphology of the Cu-Ti phase grains; the dispersed hard and brittle phases not only improve the mechanical properties of the weld, but also make the locally concentrated stress more evenly distributed.
[0016] The invention adds rare earth element La powder to AgCuTi active solder, and mixes the two uniformly by mechanical ball milling, thereby effectively avoiding component segregation during smelting of the rare earth element La, and utilizing the characteristics of the rare earth element La to effectively refine the hard and brittle phases in the weld, thereby avoiding local stress concentration in the weld and reducing the residual thermal stress of the weld.
[0017] Preferably, the mass percentage of Ti in the AgCuTi active solder is ≤5%, and the mass percentage of Ag in both Ag and Cu in the AgCuTi active solder is 68%-76%.
[0018] Preferably, the particle diameter of the AgCuTi active solder is 1 μm-100 μm, and the particle diameter of the rare earth element La powder is 10 μm-100 μm.
[0019] Preferably, the organic binder is composed of a solvent, a thickener, a dispersant, an antioxidant, a thixotropic agent and a corrosion inhibitor; the mass percentages of the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor in the organic binder are: (55%-60%), (4%-8%), (20%-30%), (5%-10%), (1%-3%), (1%-3%); the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor are added into a beaker in proportion, an inert gas is introduced into the beaker, the components in the beaker are heated to 40°C-50°C, and the components in the beaker are magnetically stirred in a constant temperature water bath for 50min-60min using a tool to obtain the prepared organic binder.
[0020] A brazing method for a ceramic sealed vacuum electrode, the brazing process comprising the following steps:
[0021] Step 1, sleeve the ceramic block on the outside of the conductive core column, so that the ceramic block and the conductive core column are connected by interference fit; the ceramic block is used to ensure that the conductive core column is isolated from the external environment;
[0022] Apply a 0.4mm-0.6mm thick Ag-based composite solder to the upper and lower outer sides of the ceramic block, and sleeve the first sleeve and the second sleeve on the upper and lower outer sides of the ceramic block respectively;
[0023] Step 2, applying a 0.4 mm to 0.6 mm thick Ag-based composite solder on the outside of the first sleeve and the second sleeve to obtain an assembly;
[0024] The stepped hole effectively prevents the flow loss of the Ag-based composite solder during the brazing process through its unique internal stepped structure, and plays a role of mechanical support.
[0025] Insert the assembly from top to bottom into the mounting hole on the flange, and the ceramic sealed vacuum electrode is assembled;
[0026] Step 3: Turn several assembled ceramic sealed vacuum electrodes upside down and place them in a vacuum brazing furnace, so that the first sleeve is located below the second sleeve, and the lower end of the conductive core column of each ceramic sealed vacuum electrode is in contact with the upper surface of the horizontally arranged graphite plate in the vacuum brazing furnace. A weight ring for pressing the flange is placed on the upper surface of the flange, and the vacuum brazing furnace is evacuated by using the three-stage pump of the vacuum brazing furnace to make the vacuum degree of the vacuum brazing furnace reach 5×10 -3 the following;
[0027] Step 4, heating before welding:
[0028] The temperature in the vacuum brazing furnace is raised from room temperature to T1, the value range of T1 is 240℃-260℃, the heating rate is ≤10℃ / min, and the temperature is kept for 30min-45min;
[0029] Heating to T1 can effectively remove low-temperature components of organic binders and water vapor in the solder;
[0030] The temperature in the vacuum brazing furnace is raised from T1 to T2, where the value range of T2 is 580°C-620°C, the heating rate is ≤10°C / min, and the heat preservation time is 15min-30min;
[0031] T2 is selected according to the melting point of the organic binder in the solder to ensure that the organic binder is completely removed at this temperature to avoid affecting the vacuum degree during subsequent brazing;
[0032] The temperature in the vacuum brazing furnace is raised from T2 to T3, the value range of T3 is 740℃-760℃, the heating rate is ≤5℃ / min, and the heat preservation time is 15min-30min;
[0033] Raising the temperature to T3 can ensure that the ceramic sealed vacuum electrode is evenly heated as a whole when it is close to the melting point of the brazing material, thus preparing for subsequent brazing.
[0034] Step 5, brazing:
[0035] The temperature in the vacuum brazing furnace is raised from T3 to T4, the value range of T4 is 870℃-900℃, the heating rate is ≤3℃ / min, the temperature is kept for 10min-20min, and the Ag-based composite brazing material is melted;
[0036] The holding time can be determined according to the amount of material entering the furnace. Too long a holding time can easily cause the reaction layer on the ceramic side to be too thick, while too short a holding time is not conducive to the full wetting of the solder, both of which will reduce the bonding strength.
[0037] Step 6, cooling down:
[0038] The temperature in the vacuum brazing furnace is reduced from T4 to T5, the value range of T5 is 810℃-820℃, the cooling rate is 15℃ / min-20℃ / min, the Ag-based composite brazing filler metal is used to weld the first sleeve to the circular plate and the upper part of the stepped hole respectively, and the Ag-based composite brazing filler metal is used to weld the second sleeve to the annular plate and the lower part of the stepped hole respectively;
[0039] The temperature in the vacuum brazing furnace is cooled from T5 to room temperature, the vacuum brazing furnace is opened, and each ceramic sealed vacuum electrode is taken out.
[0040] Rapid cooling is used in the initial stage, when the brazing material is still liquid and the shrinkage of the brazed parts is unrestrained, in order to avoid excessive reaction between the brazing material and the components.
[0041] The temperature in the vacuum brazing furnace is cooled from T5 to room temperature, the vacuum brazing furnace is opened, and each ceramic sealed vacuum electrode is taken out; the purpose of slow cooling is to minimize the residual stress caused by brazing.
[0042] Preferably, before step 1, a conductive core column pretreatment step is also included:
[0043] Step 9-1, using a hot extrusion method to coat the silver-copper alloy sheet on the conductive core column, heating the silver-copper alloy sheet and the conductive core column to 780°C-800°C, and combining the silver-copper alloy sheet and the conductive core column using an extruder to uniformly coat the silver-copper alloy sheet on the surface of the conductive core column, and obtaining a coated composite conductive core column after cooling and shaping; drawing and annealing the composite conductive core column to stably combine the silver-copper alloy sheet and the conductive core column, and finally obtaining a conductive core column with a silver-copper coating layer.
[0044] Preferably, step 9-1 further includes the following steps:
[0045] A layer of Ti metal film is formed on the surface of the conductive core column using a magnetron sputtering device:
[0046] The Ti metal film can ensure reliable bonding between the conductive core column and the ceramic block and realize wetting of the ceramic block during brazing.
[0047] The conductive core column was placed in the sputtering chamber of the magnetron sputtering instrument, and the Ti metal target was fixed on the target holder in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber was evacuated to 1.0×10 -3 Pa, the temperature of the substrate on the sample turntable is raised to 300℃-400℃ by heating the substrate for heat transfer, argon gas is introduced into the sputtering chamber, the argon gas flow rate is controlled to 25sccm-30sccm, the bias voltage is adjusted to 500V-550V, and the Ti metal target is pre-sputtered for 40min-50min to remove the oxide layer on the surface of the Ti metal target; removing the oxide layer can ensure the purity and quality of the Ti metal film;
[0048] The substrate bias voltage is adjusted to 90V-110V, the argon flow rate is controlled to be 15sccm-20sccm, the air pressure in the sputtering chamber is increased to 2.0Pa-2.5Pa, and the target seat voltage of the Ti metal target is increased to 280V-300V for glow discharge, so that the argon gas is ionized to generate argon ions. The argon ions bombard the Ti metal target, causing the metal atoms of the Ti metal target to be sputtered; the working air pressure in the sputtering chamber is adjusted to 0.6Pa-0.8Pa, and pre-sputtering is performed for 15min-20min; after the target seat voltage and current of the Ti metal target are stable, the rotation speed of the sample turntable is controlled to be 10r / min-12r / min, the target seat voltage and current of the Ti metal target are adjusted to make the power reach 260w-270w, and the sputtering is continued for 30min-40min to form a Ti metal film on the surface of the conductive core column.
[0049] In industrial production, the conductive core column and the ceramic block are often connected by interference fit, and then brazing filler metal is applied to the upper surface connection for vacuum brazing to achieve sealing.
[0050] The present invention adopts coating, temperature rising heating and drawing processes to connect the silver-copper alloy layer and the conductive core column through metal bonding force, and then adopts magnetron sputtering coating process to in-situ grow a layer of Ti metal film on the outer side of the conductive core column. Compared with the prior art, the conductive core column of the present invention is more firmly connected to the silver-copper alloy layer, and in the brazing process, the Ti metal film on the surface of the conductive core column first reacts with the ceramic block, Ti can wet the ceramic phase, enhance the bonding force between the conductive core column and the ceramic block, and make the conductive core column and the ceramic block sealed and stably and reliably connected.
[0051] Therefore, the present invention has the following beneficial effects:
[0052] The La component segregation during the melting of AgCuTi active solder is effectively avoided, and the characteristics of the rare earth element La are used to effectively refine the hard and brittle phases in the weld, thereby avoiding local stress concentration in the weld, reducing the residual thermal stress of the weld of the ceramic sealed vacuum electrode, improving the shear strength of the weld, and ensuring the reliability and stability of the ceramic sealed vacuum electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 is a cross-sectional view of one embodiment of the present invention;
[0054] Figure 2 is a SEM image of the welds of Example 1, Example 4, Example 5 and Comparative Example 2 of the present invention;
[0055] Figure 3 This is a SEM image of the weld of Example 5 of the present invention. DETAILED DESCRIPTION
[0056] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0057] Example 1
[0058] The wide-range ionization vacuum gauge in the vacuum equipment comprises a cathode, an anode, a collector and a flange. The present invention is used for brazing the collector and the flange. The collector is the ceramic sealed vacuum electrode in the present invention.
[0059] like Figure 1 The embodiment shown is a ceramic sealed vacuum electrode, which passes through a flange 6 made of Al2O3 ceramic material; the ceramic sealed vacuum electrode includes a conductive core column 4 made of 316 stainless steel, an Al2O3 ceramic block sleeved on the conductive core column, a first sleeve 1 and a second sleeve 3; the first sleeve and the second sleeve are both made of Kovar alloy; the Al2O3 ceramic block includes a cylinder 21, a circular plate 22 arranged at the upper end of the cylinder and an annular plate 23 arranged in the middle of the cylinder, the inner side surface of the first sleeve is brazed to the lower surface and the outer side surface of the circular plate respectively, and the inner side surface of the second sleeve is brazed to the lower surface and the outer side surface of the annular plate respectively; a stepped hole 61 is provided on the flange, the outer side surface of the first sleeve is brazed to the upper part of the inner side surface of the stepped hole, and the outer side surface of the second sleeve is brazed to the lower part of the inner side surface of the stepped hole.
[0060] The brazing adopts Ag-based composite brazing material, which is composed of mixed brazing material and organic binder. The mass percentage of the mixed brazing material is 85%, and the balance is organic binder.
[0061] The mixed solder consists of rare earth element La powder and AgCuTi active solder, wherein the mass percentage of the rare earth element La powder in the mixed solder is 0.5%, and the balance is AgCuTi active solder; the rare earth element La powder and the AgCuTi active solder are mechanically ball-milled to obtain the mixed solder, and the mixed solder is mixed with an organic binder to obtain the prepared Ag-based composite solder.
[0062] The mass percentage of Ti in the AgCuTi active solder is 3%; the mass percentage of Ag in the AgCuTi active solder is 72%, and the mass percentage of Cu is 28%.
[0063] The particle diameter of the AgCuTi active solder is 80 μm, and the particle diameter of the rare earth element La powder is 850 μm.
[0064] The organic binder consists of a solvent, a thickener, a dispersant, an antioxidant, a thixotropic agent and a corrosion inhibitor; the mass percentages of the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor in the organic binder are: 58%, 8%, 20%, 10%, 1% and 3%; the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor are added into a beaker in proportion, an inert gas is introduced into the beaker, the components in the beaker are heated to 45 DEG C, and the components in the beaker are magnetically stirred in a constant temperature water bath for 55 minutes by using a tool to obtain the prepared organic binder.
[0065] A brazing method for a ceramic sealed vacuum electrode, the brazing process comprising the following steps:
[0066] Before brazing connection, the surfaces of the Al2O3 ceramic block and the 316 stainless steel conductive core column to be brazed are ground and polished step by step with sandpaper until there is no trace, and then the Al2O3 ceramic block and the 316 stainless steel conductive core column are ultrasonically cleaned in an alcohol solution, and finally dried to obtain the Al2O3 ceramic block and the 316 stainless steel conductive core column after surface treatment;
[0067] Step 01, using hot extrusion method to coat the silver-copper alloy sheet 8 on the conductive core column, heating the silver-copper alloy sheet and the conductive core column to 800°C, and combining the silver-copper alloy sheet and the conductive core column by using an extruder, so that the silver-copper alloy sheet is evenly coated on the surface of the conductive core column, and after cooling and shaping, a coated composite conductive core column is obtained; the composite conductive core column is drawn and annealed to stably combine the silver-copper alloy sheet and the conductive core column, and finally a conductive core column with a silver-copper coating layer is obtained.
[0068] Step 02, using a magnetron sputtering device to form a layer of Ti metal film 7 on the surface of the conductive core column:
[0069] The conductive core column was placed in the sputtering chamber of the magnetron sputtering instrument, and the Ti metal target was fixed on the target holder in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber was evacuated to 1.0×10 -3 Pa, the temperature of the substrate on the sample turntable was raised to 350°C by heating the substrate for heat transfer, argon gas was introduced into the sputtering chamber, the argon gas flow rate was controlled to 30 sccm, the bias voltage was adjusted to 540 V, and the Ti metal target was pre-sputtered for 50 minutes to remove the oxide layer on the surface of the Ti metal target;
[0070] The substrate bias voltage was adjusted to 100 V, the argon flow rate was controlled to be 18 sccm, the air pressure in the sputtering chamber was increased to 2.3 Pa, and the target seat voltage of the Ti metal target was increased to 290 V for glow discharge, so that the argon gas was ionized to generate argon ions. The argon ions bombarded the Ti metal target, causing the metal atoms of the Ti metal target to be sputtered. The working air pressure in the sputtering chamber was adjusted to 0.7 Pa, and pre-sputtering was performed for 18 minutes. After the target seat voltage and current of the Ti metal target were stable, the rotation speed of the sample turntable was controlled to be 11 r / min, and the target seat voltage and current of the Ti metal target were adjusted to make the power reach 265 w. The sputtering was continued for 30 minutes to form a 0.8 μm thick Ti metal film 7 on the surface of the conductive core column.
[0071] Step 1, sleeve the ceramic block on the outside of the conductive core column, so that the ceramic block and the conductive core column are connected by interference fit;
[0072] Apply a 0.5 mm thick Ag-based composite solder 5 to the upper and lower outer sides of the ceramic block, and sleeve the first sleeve and the second sleeve on the upper and lower outer sides of the ceramic block respectively;
[0073] Step 2: Apply a 0.55 mm thick Ag-based composite solder to the outside of the first sleeve and the second sleeve to obtain an assembly; insert the assembly from top to bottom into the mounting hole provided on the flange, and the ceramic sealed vacuum electrode is assembled;
[0074] Step 3: Turn the assembled ceramic sealed vacuum electrodes upside down and place them in a vacuum brazing furnace, so that the first sleeve is located below the second sleeve, and the lower end of the conductive core column of each ceramic sealed vacuum electrode is in contact with the upper surface of the horizontally arranged graphite plate in the vacuum brazing furnace. A weight ring for pressing the flange is placed on the upper surface of the flange, and the vacuum brazing furnace is evacuated by using the three-stage pump of the vacuum brazing furnace to make the vacuum degree of the vacuum brazing furnace reach 5×10 -3 the following;
[0075] Step 4, heating before welding:
[0076] The temperature in the vacuum brazing furnace is raised from room temperature to T1, where the value range of T1 is 250°C, the heating rate is ≤10°C / min, and the temperature is kept for 40 minutes;
[0077] The temperature in the vacuum brazing furnace is raised from T1 to T2, where the value range of T2 is 600°C, the heating rate is ≤10°C / min, and the temperature is kept for 25 minutes;
[0078] The temperature in the vacuum brazing furnace is raised from T2 to T3, the value range of T3 is 750°C, the heating rate is ≤5°C / min, and the temperature is kept for 20 minutes;
[0079] Step 5, brazing:
[0080] The temperature in the vacuum brazing furnace is raised from T3 to T4, the value range of T4 is 880°C, the heating rate is ≤3°C / min, and the temperature is kept for 15 minutes, and the Ag-based composite brazing material is melted;
[0081] Step 6, cooling down:
[0082] The temperature in the vacuum brazing furnace is lowered from T4 to T5, the value range of T5 is 815°C, the cooling rate is 18°C / min, the Ag-based composite brazing filler metal is used to weld the first sleeve to the circular plate and the upper part of the stepped hole respectively, and the Ag-based composite brazing filler metal is used to weld the second sleeve to the annular plate and the lower part of the stepped hole respectively;
[0083] The temperature in the vacuum brazing furnace is cooled from T5 to room temperature, the vacuum brazing furnace is opened, and each ceramic sealed vacuum electrode is taken out.
[0084] Example 2
[0085] The mass percentages of the solvent, thickener, dispersant, antioxidant, thixotropic agent and corrosion inhibitor in the organic binder of Example 2 are: 59%, 5%, 25%, 8%, 2% and 1%.
[0086] Sputtering was continued for 35 min to form a 1.2 μm thick Ti metal film on the surface of the conductive core column;
[0087] The other structures and methods in Example 2 are the same as those in Example 1;
[0088] Example 3
[0089] The mass percentages of the solvent, thickener, dispersant, antioxidant, thixotropic agent and corrosion inhibitor in the organic binder in Example 3 are: 60%, 5%, 22%, 9%, 2% and 2%.
[0090] Sputtering was continued for 40 min to form a 1.5 μm thick Ti metal film on the surface of the conductive core column;
[0091] The other structures and methods in Example 3 are the same as those in Example 1;
[0092] Example 4
[0093] The mass percentage of the mixed solder of the Ag-based composite solder in Example 4 is 90%, and the mass percentage of the rare earth element La powder in the mixed solder is 1.5%;
[0094] The mass percentages of the solvent, thickener, dispersant, antioxidant, thixotropic agent and corrosion inhibitor in the organic binder are: 59%, 4%, 30%, 5%, 1% and 1%.
[0095] Sputtering was continued for 30 minutes to form a 0.8 μm thick Ti metal film on the surface of the conductive core column.
[0096] The other structures and methods in Example 4 are the same as those in Example 1;
[0097] Example 5
[0098] The mass percentage of the mixed solder of the Ag-based composite solder in Example 5 is 88%, and the mass percentage of the rare earth element La powder in the mixed solder is 2.5%;
[0099] The mass percentages of the solvent, thickener, dispersant, antioxidant, thixotropic agent and corrosion inhibitor in the organic binder are: 58%, 6%, 25%, 8%, 2% and 1%.
[0100] Sputtering was continued for 30 minutes to form a 0.8 μm thick Ti metal film on the surface of the conductive core column.
[0101] The other structures and methods in Example 5 are the same as those in Example 1;
[0102] Comparative Example 1
[0103] The Al2O3 ceramic block and the 316 stainless steel conductive core column are brazed and connected by using AgCuTi active brazing filler metal, wherein the AgCuTi active brazing filler metal is (AgCu)97Ti3, and the AgCu is Ag72Cu28.
[0104] Comparative Example 2
[0105] Apply 0.5mm thick AgCuTi active solder to the upper and lower parts of the outer side of the ceramic block, and respectively cover the first and second sleeves on the upper and lower parts of the outer side of the ceramic block; apply 0.55mm thick AgCuTi active solder to the outer sides of the first and second sleeves to obtain an assembly, and vacuum braze the assembly. The AgCuTi active solder is (AgCu)97Ti3, and AgCu is Ag72Cu28.
[0106] Performance Testing
[0107] 1. The ceramic sealed vacuum electrodes obtained in Examples 1 to 3 and Comparative Example 1 were placed on a universal testing machine to test the shear strength of the weld between the Al2O3 ceramic block and the 316 stainless steel conductive core column. The results are shown in Table 1:
[0108] Weld Shear strength / MPa Example 1 177.83 Example 2 208.64 Example 3 189.58 Comparative Example 1 150.85
[0109] Table 1
[0110] It can be seen that the shear strength of the welds of Examples 1 to 3 is better than that of Comparative Example 1; as the thickness of the Ti metal film increases, the shear strength of the weld increases first and then decreases, among which, when the thickness of the Ti metal film is 1.2 μm, the shear strength of the weld is as high as 208.64 MPa.
[0111] The ceramic sealed vacuum electrodes obtained in Example 1, Example 4, Example 5 and Comparative Example 2 were placed on a universal testing machine to test the shear strength of the weld between the outer side of the Al2O3 ceramic block and the first sleeve. The ceramic sealed vacuum electrodes were placed on a nanoindenter to test the welds between the outer side of the Al2O3 ceramic block and the first sleeve and the second sleeve. The residual stress of the weld was calculated according to the Suresh model. The results are shown in Table 2:
[0112]
[0113]
[0114] Table 2
[0115] It can be seen that the shear strength of the welds of Example 1, Example 4 and Example 5 is better than that of Comparative Example 2; with the increase of the rare earth element La content, the shear strength of the weld shows a gradually increasing trend, while the residual stress shows a gradually decreasing trend. Among them, when the La content is 2.5%, the shear strength of the weld is as high as 199.25MPa, and the residual stress value is 0.42GPa.
[0116] like Figure 2 As shown, the welding seam between the outer side of the Al2O3 ceramic block and the first sleeve of the ceramic sealed vacuum electrode of Example 1, Example 4, Example 5 and Comparative Example 2 was inspected by scanning electron microscope, wherein: Figure 2 Figures (b) to (d) correspond to Example 1, Example 4, and Example 5, respectively; Figure (a) corresponds to Example 2;
[0117] from Figure 2 It can be seen that with the increase of La content in the Ag-based composite solder, the Cu-Ti brittle phase in the weld is refined, the residual stress distribution of the weld is uniformed, the local stress concentration is reduced, and the mechanical properties of the weld are significantly improved.
[0118] like Figure 3 As shown, the weld of the ceramic sealed vacuum electrode of Example 5 was completely filled with solder, and no holes or microcracks were observed; combined with EDS and XRD analysis, it was determined that the weld of the ceramic sealed vacuum electrode included Ti3Cu3O, Ag(s, s), Cu(s, s), TiCu and TiFe2 phases.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A ceramic sealed vacuum electrode, the ceramic sealed vacuum electrode passing through a flange (6); wherein: The ceramic sealed vacuum electrode comprises a conductive core column (4), a ceramic block sleeved on the conductive core column, a first sleeve (1) and a second sleeve (3); the first sleeve and the second sleeve are both made of Kovar alloy; the ceramic block comprises a cylinder (21), a circular plate (22) arranged at the upper end of the cylinder and an annular plate (23) arranged at the middle of the cylinder; the inner side surface of the first sleeve is respectively brazed to the lower surface and the outer side surface of the circular plate, and the inner side surface of the second sleeve is respectively brazed to the lower surface and the outer side surface of the annular plate; a stepped hole (61) is provided on the flange, the outer side surface of the first sleeve is brazed to the upper part of the inner side surface of the stepped hole, and the outer side surface of the second sleeve is brazed to the lower part of the inner side surface of the stepped hole.
2. The ceramic sealed vacuum electrode according to claim 1, characterized in that: The brazing adopts Ag-based composite brazing material, which is composed of mixed brazing material and organic binder, the mass percentage of the mixed brazing material is 85%-90%, and the balance is organic binder; The mixed solder consists of rare earth element La powder and AgCuTi active solder, wherein the mass percentage of the rare earth element La powder in the mixed solder is 0.5%-2.5%, and the balance is AgCuTi active solder; the rare earth element La powder and the AgCuTi active solder are mechanically ball-milled to obtain the mixed solder, and the mixed solder is mixed with an organic binder to obtain the prepared Ag-based composite solder.
3. The ceramic sealed vacuum electrode according to claim 1, characterized in that: The conductive core column is made of molybdenum, stainless steel or oxygen-free copper.
4. The ceramic sealed vacuum electrode according to claim 1, characterized in that: The ceramic block is made of Al2O3 or zirconium oxide material.
5. The ceramic sealed vacuum electrode according to claim 2, characterized in that: The mass percentage of Ti in the AgCuTi active solder is ≤5%, and the mass percentage of Ag in both Ag and Cu in the AgCuTi active solder is 68%-76%.
6. The Ag-based composite solder for ceramic sealed vacuum electrode according to claim 2, characterized in that: The particle diameter of the AgCuTi active solder is 1 μm-100 μm, and the particle diameter of the rare earth element La powder is 10 μm-100 μm.
7. The ceramic sealed vacuum electrode according to claim 2, 5 or 6, characterized in that: The organic binder consists of a solvent, a thickener, a dispersant, an antioxidant, a thixotropic agent and a corrosion inhibitor; the mass percentages of the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor in the organic binder are: (55%-60%), (4%-8%), (20%-30%), (5%-10%), (1%-3%), (1%-3%); the solvent, the thickener, the dispersant, the antioxidant, the thixotropic agent and the corrosion inhibitor are added into a beaker in proportion, an inert gas is introduced into the beaker, each component in the beaker is heated to 40-50° C., and each component in the beaker is magnetically stirred in a constant temperature water bath for 50 minutes to 60 minutes by a tool to obtain the prepared organic binder.
8. A brazing method for a ceramic sealed vacuum electrode according to claim 2, characterized in that: The brazing process includes the following steps: Step 1, sleeve the ceramic block on the outside of the conductive core column, so that the ceramic block and the conductive core column are connected by interference fit; Applying Ag-based composite solder (5) with a thickness of 0.4 mm to 0.6 mm on the upper and lower parts of the outer side of the ceramic block, and sleeve the first sleeve and the second sleeve on the upper and lower parts of the outer side of the ceramic block respectively; Step 2, applying a 0.4 mm to 0.6 mm thick Ag-based composite solder on the outside of the first sleeve and the second sleeve to obtain an assembly; Insert the assembly from top to bottom into the mounting hole on the flange, and the ceramic sealed vacuum electrode is assembled; Step 3: Turn several assembled ceramic sealed vacuum electrodes upside down and place them in a vacuum brazing furnace, so that the first sleeve is located below the second sleeve, and the lower end of the conductive core column of each ceramic sealed vacuum electrode is in contact with the upper surface of the horizontally arranged graphite plate in the vacuum brazing furnace. A weight ring for pressing the flange is placed on the upper surface of the flange, and the vacuum brazing furnace is evacuated by using the three-stage pump of the vacuum brazing furnace to make the vacuum degree of the vacuum brazing furnace reach 5×10 -3 the following; Step 4, heating before welding: The temperature in the vacuum brazing furnace is raised from room temperature to T1, the value range of T1 is 240℃-260℃, the heating rate is ≤10℃ / min, and the temperature is kept for 30min-45min; The temperature in the vacuum brazing furnace is raised from T1 to T2, where the value range of T2 is 580°C-620°C, the heating rate is ≤10°C / min, and the heat preservation time is 15min-30min; The temperature in the vacuum brazing furnace is raised from T2 to T3, the value range of T3 is 740℃-760℃, the heating rate is ≤5℃ / min, and the heat preservation time is 15min-30min; Step 5, brazing: The temperature in the vacuum brazing furnace is raised from T3 to T4, the value range of T4 is 870℃-900℃, the heating rate is ≤3℃ / min, the temperature is kept for 10min-20min, and the Ag-based composite brazing material is melted; Step 6, cooling down: The temperature in the vacuum brazing furnace is reduced from T4 to T5, the value range of T5 is 810℃-820℃, the cooling rate is 15℃ / min-20℃ / min, the Ag-based composite brazing filler metal is used to weld the first sleeve to the circular plate and the upper part of the stepped hole respectively, and the Ag-based composite brazing filler metal is used to weld the second sleeve to the annular plate and the lower part of the stepped hole respectively; The temperature in the vacuum brazing furnace is cooled from T5 to room temperature, the vacuum brazing furnace is opened, and each ceramic sealed vacuum electrode is taken out.
9. The brazing method of ceramic sealed vacuum electrode according to claim 8, characterized in that: Before step 1, a conductive core column pretreatment step is also included: Step 9-1, using a hot extrusion method to coat the silver-copper alloy sheet (8) on the conductive core column, heating the silver-copper alloy sheet and the conductive core column to 780° C.-800° C., and combining the silver-copper alloy sheet and the conductive core column by using an extruder, so that the silver-copper alloy sheet is evenly coated on the surface of the conductive core column, and after cooling and shaping, a coated composite conductive core column is obtained; the composite conductive core column is drawn and annealed to stably combine the silver-copper alloy sheet and the conductive core column, and finally a conductive core column with a silver-copper coating layer is obtained.
10. The brazing method of ceramic sealed vacuum electrode according to claim 9, characterized in that: After step 9-1, the following steps are also included: A layer of Ti metal film (7) is formed on the surface of the conductive core column by using a magnetron sputtering device: The conductive core column was placed in the sputtering chamber of the magnetron sputtering instrument, and the Ti metal target was fixed on the target holder in the sputtering chamber of the magnetron sputtering instrument. The sputtering chamber was evacuated to 1.0×10 -3 Pa, the temperature of the substrate on the sample turntable is raised to 300°C-400°C by heating the substrate for heat transfer, argon gas is introduced into the sputtering chamber, the argon gas flow rate is controlled to 25sccm-30sccm, the bias voltage is adjusted to 500V-550V, and the Ti metal target is pre-sputtered for 40min-50min to remove the oxide layer on the surface of the Ti metal target; The substrate bias voltage is adjusted to 90V-110V, the argon flow rate is controlled to be 15sccm-20sccm, the air pressure in the sputtering chamber is increased to 2.0Pa-2.5Pa, and the target seat voltage of the Ti metal target is increased to 280V-300V for glow discharge, so that the argon gas is ionized to generate argon ions. The argon ions bombard the Ti metal target, causing the metal atoms of the Ti metal target to be sputtered; the working air pressure in the sputtering chamber is adjusted to 0.6Pa-0.8Pa, and pre-sputtering is performed for 15min-20min; after the target seat voltage and current of the Ti metal target are stable, the rotation speed of the sample turntable is controlled to be 10r / min-12r / min, the target seat voltage and current of the Ti metal target are adjusted to make the power reach 260w-270w, and the sputtering is continued for 30min-40min to form a Ti metal film on the surface of the conductive core column.
Citation Information
Patent Citations
Sensor
CN102787896A
Electrode embedded welding flange electrode and application thereof
CN113675690A
AgCuTi-based composite brazing filler metal and brazing method for connecting AlN ceramic and Cu through AgCuTi-based composite brazing filler metal
CN114769940A
Preparation method of high-thermal-conductivity graphite thick plate based on welding process
CN115043662A
Ceramic-metal feedthrough assembly, in particular for cardiac or neural stimulation, and method of manufacturing it
EP0269007A1